2017
DOI: 10.1186/s12967-017-1284-7
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid attenuates acute lung injury through induction of type 2 macrophage

Abstract: BackgroundAcute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are severe inflammatory lung diseases. Methylprednisolone (MP) is a common drug against inflammation in clinic. In this study, we aim to investigate the protective effect of MP on ALI and potential mechanisms.MethodsMale BABL/c mice were injected through tail vein using lipopolysaccharide (LPS, 5 mg/kg) with or without 5 mg/kg MP. Lung mechanics, tissue injury and inflammation were examined. Macrophage subsets in the lung were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 35 publications
4
97
0
Order By: Relevance
“…In addition, it was important to exclude the nonsigni cantly changed genes by applying an FDR (false discovery rate) of 0.05. This study supports the rising interest in macrophages that shift their polarisation state and function from pro-in ammatory to anti-in ammatory phenotype, thus contributing to resolving in ammation and improvement of tissue repair after injury [32]. Furthermore, it is known that dysregulation of macrophage polarisation contributes to the development of various in ammatory diseases [33].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, it was important to exclude the nonsigni cantly changed genes by applying an FDR (false discovery rate) of 0.05. This study supports the rising interest in macrophages that shift their polarisation state and function from pro-in ammatory to anti-in ammatory phenotype, thus contributing to resolving in ammation and improvement of tissue repair after injury [32]. Furthermore, it is known that dysregulation of macrophage polarisation contributes to the development of various in ammatory diseases [33].…”
Section: Discussionsupporting
confidence: 82%
“…This is especially true for MΦ-IL10, which can be polarised by administration of GC. Recent publications reported an increase in M2-MΦ after GC treatment and an improved outcome in acute lung injury 15 . Patients with therapeutically polarised MΦ-IL10 recovered with a better outcome from asthma 16 .…”
mentioning
confidence: 97%
“…[42,43] Animal experiments in recent years have provided evidence for the use of glucocorticoids to reduce inflammation, the attenuation of acute lung injury, and reduction in mortality during the acute phase of severe disease. [44,45] However, other studies have suggested that glucocorticoid therapy in ARDS is not necessary, and may even aggravate the clinical picture. The use of hydrocortisone improves lung function in sepsis-associated ARDS, but no significant survival benefit has been observed in these patients.…”
Section: Discussionmentioning
confidence: 99%